Structure of a Munn semigroup of finite rank every stable order of which is fundamental or antifundamental - Derech, V. D. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We describe the structure of a Munn semigroup of finite rank every stable order of which is fundamental or antifundamental.